On Some α-Proper Mapping Types (Journal of the College of Basic Education, 2023)
The main aim of this paper is to study some new classes of proper mapping which are (α- proper , α*- proper, α**- proper)mappings and discussion the relation between them .as well as several properties of these mappings are prove